Comparative study of transepithelial versus alcohol-assisted photorefractive keratectomy - Marwa M Gaber; Mohamed Y.S. Saif; Hany S.E. Elsaftawy; Ahmad T. Gouda (Delta Journal of Ophthalmology)
Aim The aim of this study was to compare the clinical, refractive, and visual outcome of transepithelial photorefractive keratectomy (T-PRK) to the alcohol-assisted photorefractive keratectomy (AA-PRK).